Uwarunkowania wzrostu sektora małych i średnich przedsiębiorstw w Polsce w latach 1990-2011 - Gasiński, Wojciech; Misztal, Anna (Gospodarka w Praktyce i Teorii, 2011)
This article aims to present the analysis of the development of small and mediumsized enterprises in Poland in the years 1990-2011. Political changes to which the Republic of Poland invaded after 1989 led to the emergence of a market-oriented economies. New economic system, has discovered plenty of opportunities for enterprise development and contributed to the development of small and medium enterprises. The development of small and medium enterprises is crucial for the correct functioning of the economy and the mechanisms in place. The intention of the article is to determine the degree of development of the sector by carrying out a study on the evolution of the number of enterprises depending on the specific macroeconomic conditions. Analyses have been developed based on data from the Polish Agency for Enterprise Development, Central Statistical Office and Eurostat